PERAN MEDIATOR WORK ENGAGEMENT: PENGARUH WORK – LIFE BALANCE TERHADAP TURNOVER INTENTION - Sjahruddin, Herman; Arsanti, Galuh; Mahmud, Mahmud; Hijaz, Zulkifly; Rahmat, Amri Nur; Alam, Syamsul (Universitas Riau Kepulauan, 2025)
Work-life balance is stated as a crucial factor in influencing employee well-being and retention. While an imbalance between work demands and personal life can trigger stress, fatigue, and ultimately, turnover intention, the causality does not always have a direct effect. The role of work engagement as a mediator is very important. This research was conducted on 150 millennial generation employees in Makassar City, the questionnaire was distributed via google form. There were 21 questionnaires that were declared defective, leaving 129 questionnaires. Determination of the data analysis unit was carried out using a purposive technique where sampling was drawn using certain considerations, including the age range of 29-44 years and being married and working. Data analysis used SmartPLS (partial least square) 4.0 software. The results of the study prove that the better the work-life balance, the higher the level of employee involvement and enthusiasm for their work, that work-life balance provides significant positive results on work engagement. Improvements in work-life balance trigger employees' desire to quit their jobs, that work-life balance has a significant positive effect on turnover intention. The higher the employee engagement towards their work becomes a response to the high intention of employees to resign. The better the work-life balance, the higher the turnover intention through high employee work engagement.